Cognitive impairment and chemotherapy: a brief overview. (October 2017) - Vitali, Milena; Ripamonti, Carla Ida; Roila, Fausto; Proto, Claudia; Signorelli, Diego; Imbimbo, Martina; Corrao, Giulia; Brissa, Angela; Rosaria, Gallucci; de Braud, Filippo; Garassino, Marina Chiara; Lo Russo, Giuseppe
Highlights: Chemotherapy has significantly increased overall survival in cancer patients. Chemotherapeutic drugs cause various side effects. An emerging side effect is the decline in cognitive function. Cognitive impairment has a serious impact on quality of life (QoL). Abstract: Patients with cancer are experiencing long-term survival following chemotherapy, but the treatment may also be associated with short and long-term toxicity, including the possibility of cognitive dysfunction. A literature overview indicated a significant association between chemotherapy and cognitive impairment but prospective longitudinal research is warranted to examine the degree and persisting nature of this decline. Although chemotherapeutic agents are unlikely to cross the blood-brain barrier, it has been alleged that the occurrence of neurotoxicity is linked to the pro-inflammatory cytokine pathways. Moreover in most cases many other factors could play an ancillary and concomitant role. The contribution of hormone therapy as well as emotional, social, behavioural and genetic factors should always be considered. Especially physical activity and cognitive training appear promising in the management of cognitive impairment but additional studies are required to establish their efficacy.